A national analysis of the content knowledge of Turkish physical education teacher education students - DERVENT, FATİH (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
Background: Content knowledge is universally acknowledged as one of several knowledge bases that inform pedagogical content knowledge (PCK). Content knowledge has been both hypothesized and demonstrated to influence PCK in two ways. First, teachers must know the rules, safety, etiquette, technique, and tactics of a movement form to teach it. This domain of content knowledge is called common content knowledge (CCK), that is the knowledge that one needs to perform the content. Second, in addition teachers must also know how to select, design, and represent instructional tasks that describe the rules, safety, etiquette, techniques, and tactics to students in ways that they will understand and respond to errors by students in terms of rules, safety, etiquette, techniques, and tactics, that is called specialized content knowledge (SCK) for physical education. Purpose: This study examined the effects of teacher training on the levels of soccer and gymnastics CCK and SCK that preservice teachers learn in physical education teacher education (PETE) programs. Method: Participants were 1514 undergraduate physical education teacher education students (i.e. freshman n = 435; sophomore n = 397; junior n = 383; senior n =299) enrolled in 16 universities that were representative of all geographical regions of Turkey. A cross-sectional analysis was conducted to examine the depth of CCK and SCK. To measure the depth of CCK, we used validated multiple-choice soccer and gymnastics tests. Content maps were used to examine the depth of SCK. To analyze the differences in the CCK and SCK scores of soccer and gymnastics at each grade level, a one-way ANOVA test, and Bonferroni follow-up test was used. To compare the differences between the entrance and exit CCK and SCK levels, t-test was utilized. In addition, we conducted an analysis of content class syllabi and interviews with the instructors (soccer n = 8; gymnastics n = 9) to determine the extent to which the content and delivery of the courses distinguished between CCK and SCK. Findings: Regardless of the grade level, PETE students' CCK scores were below the success criterion of 60% that is being used in the Turkish Higher Education system (the soccer CCK= 51.85%; the gymnastics CCK = 49.91%). In terms of SCK, scores were below the 3.0 benchmark of adequate SCK (the soccer SCK = 0.23; the gymnastics SCK = 0.20). Despite the significance of differences between CCK and SCK scores among grade levels, the scores were very low showing little content knowledge. Conclusion: Freshman data showed that neither CCK nor SCK in soccer programs. The students in PETE programs examined in this study demonstrated limited improvement in CCK and SCK from freshmen to seniors. Turkish PETE programs must be redesigned to teach each domain of content knowledge. Results of this study may help to change the prevalent, though incorrect, mindset that students obtain CCK and SCK by learning how to perform a sport.
Keywords: Common content knowledge; specialized content knowledge; content development; preservice teaching; professional knowledge; SPECIALIZED CONTENT KNOWLEDGE; PEDAGOGICAL CONTENT KNOWLEDGE; COMMON CONTENT KNOWLEDGE; CONTENT MAPS; TASK; VALIDATION